Korruption in Unternehmen: Typologie und Prävention - Sabine Schmidt (Fachhochschule Pforzheim, 2004)
Der Beitrag beschreibt anhand eines Fallbeispiels das Phänomen der Korruption im geschäftlichen Verkehr, die daraus für Unternehmen resultierenden Schäden und zeigt Präventionsmöglichkeiten auf. – – The author presents several case studies on the phenomenon of corruption. She shows the damages caused by corruption as well as the consequences for companies affected by it. She finally derives practical proposals to prevent corruption in business companies.
urn:nbn:de:bsz:951-opus-722
Keywords: 650; Unternehmen; Auftragsabwicklung; Interne Revision; Kontrolle